Music therapy reduces fatigue of the patients undergoing autologous hematopoietic stem cells transplantation - Dóro, Carlos Antonio (2025)
Introduction: Autologous hematopoietic stem cell transplantation (HSCT) is a therapeutic medical treatment for various neoplastic hematologic, congenital, genetic, or acquired disorders. In this procedure which combines high-dose chemotherapy and/or radiotherapy and has a high degree of cytotoxicity, the patient experiences solitary confinement, which causes psychological distress, anxiety, mood disorder, fatigue, nausea, and pain and can lead him/her to depression. Objective: Evaluate the effectiveness of music therapy intervention for fatigue in patients undergoing autologous hematopoietic stem cell transplantation. Methods: This is a randomized clinical trial patients (n=151) were selected randomly were selected for the Experimental Music Therapy Group (EMG, n=76) which received the intervention, and for the Control Group (CG, n=75) which received only standard treatment. Interventions of live music were made using music therapy methods and techniques by a qualified music therapist. For assessment and quantification, the visual analog scale (VAS), and piper fatigue scale (PFS) were used. Results: The analysis and statistical tests applied were considered statistically significant. (PFS) Score Total (EMG) Baseline 7.1 (CG) 6.7 p=0.30 follow up (EMG) 2.4 (CG) 5.7=2.4 p<0.001 (VAS) before intervention 6.45 p=0.89 after intervention 2.52 p<0.001. Conclusion: Music therapy reduces fatigue of the undergoing autologous hematopoietic stem cell transplantation, providing bio-psychosocial welfare.